Relation between magnetosonic waves and pitch angle anisotropy of warm protons - Joseph, J.; Jaynes, A. N.; Ma, Q.; Hartley, D. P.; Usanova, M. E.; Li, W. (Frontiers in Astronomy and Space Sciences, 2022)
In the past decade, many observations of transversely heated low energy protons were reported in the inner magnetosphere. Interestingly, most of the time heated protons were observed along with magnetosonic waves. Due to the strong correlation, it was often assumed that magnetosonic waves were responsible for the heating of low energy protons. By performing a case study under unusually disturbed geomagnetic conditions, this paper unravels the controversial relationship between the observed pitch angle anisotropy of warm protons and the accompanying magnetosonic waves in the inner magnetosphere. We perform a comparative analysis involving two nearly identical cases of pitch angle anisotropy of warm protons in low L-shell region – one with magnetosonic waves and one without them. It is found that magnetosonic waves are not responsible for primary heating of low-energy protons and may just marginally alter the shape of the distribution of heated protons in the events analyzed. Based on the recent Cluster and POLAR observations, we also show how the recirculated polar wind plasma in the Earth’s magnetosphere can cause the concurrent appearance of heated protons and magnetosonic waves.